PENGARUH BUDAYA ORGANISASI DAN DISIPLIN KERJA TERHADAP KINERJA PEGAWAI BADAN KESATUAN BANGSA DAN POLITIK (KESBANGPOL) PROVINSI PAPUA BARAT DAYA - Abner Kareth; Andi Irwan; Mervin Komber (JURNAL LENTERA BISNIS, 2026)
This study is entitled "The Influence of Organizational Culture and Work Discipline on the Performance of Employees at the National Unity and Politics Agency (Kesbangpol) in Southwest Papua Province." This research is motivated by the importance of employee performance as a determining factor in the success of a government agency in carrying out its public service duties and functions. The purpose of this study is to analyze the influence of organizational culture and work discipline on the performance of employees at the National Unity and Politics Agency (Kesbangpol) in Southwest Papua Province. This study uses a quantitative approach with a survey method. The population in this study was all employees at the agency, with a purposive sampling technique used. Data collection was conducted using a questionnaire compiled based on indicators of the Work Environment, Competence, and employee performance in accordance with relevant theories. The data obtained will be analyzed using validity and reliability tests and multiple linear regression to determine the extent of the influence of the Work Environment and Competence on employee performance. This research is expected to contribute to the development of human resource management policies in local governments, particularly in efforts to improve employee performance through strategies to improve the Work Environment and provide fair and proportional Competence. The results of this study show a sig. 0.015 > 0.05, indicating that Organizational Culture does not significantly influence employee performance. The Work Discipline variable, with a sig. 0.000 < 0.05, indicates that the Work Discipline variable has a significant influence on employee performance. Simultaneously, both variables have a significant influence on employee performance, with a sig. 0.00 < 0.05.